The Origin of Synergetic Effect in Mixed Mn-Co Oxide with Spinel Structure for Catalytic Oxidation of CO - Olga A. Bulavchenko; Vladimir A. Rogov; Evgeny Yu. Gerasimov; Egor E. Aydakov; Anna M. Kremneva (Inorganics)
In this work, the origin of the synergetic effect in mixed MnxCo3-xO4 oxides with the spinel structure in the CO oxidation reaction was tested. A series of MnxCo3-x oxide catalysts were synthesized by the coprecipitation method with further calcination at 600 °C and varying manganese content from x = 0 to x = 3. The catalysts were characterized using XRD, TEM, N2 adsorption, TPR, EXAFS, and XPS. The catalytic activity of MnxCo3-x oxide catalysts was tested in CO oxidation reactions. The addition of manganese to cobalt oxide results in the formation of mixed Mn-Co oxides based on a cubic or tetragonal spinel structure, a change in microstructural properties, such as surface area and crystal size, as well as local distortions and a decrease in the surface concentration of Co ions and Co in the octahedral sites in spinel structure; it also decreases catalyst reducibility. For all catalysts, the activity of CO oxidation decreases as follows: Mn0.1Co2.9 > Co3O4~Mn0.3Co2.7 > Mn0.5Co2.5 > MnOx > Mn0.7Co2.3 > Mn0.9Co2.1~Mn1.1Co1.9~Mn2.5Co0.5 > Mn2.9Co0.1 > Mn1.7Co1.3 > Mn2.1Co0.9 > Mn1.3Co1.7~Mn1.5Co1.5~Mn2.3Co0.7. The Mn0.1Co2.9 catalyst displays the best catalytic activity, which is attributed to its small crystal size and the maximum surface ratio between Co3+ and Co2+. A further increase in the manganese content (x > 0.3) provokes drastic changes in the catalytic properties due to a decrease in the cobalt content on the surface and in the volume of mixed oxide, changes in the oxidation states of cations, and structure transformation.